2012
DOI: 10.1177/0895904812453998
|View full text |Cite
|
Sign up to set email alerts
|

Examining Elementary Social Studies Marginalization

Abstract: Utilizing data from the National Center for Education Statistics Schools and Staffing Survey (SASS), a multilevel model (Hierarchical Linear Model) was developed to examine the association of teacher/classroom and state level indicators on reported elementary social studies instructional time. Findings indicated that state testing policy was a significant predictor of elementary teachers’ reported time spent on social studies instruction. Teachers’ perceptions of workplace autonomy and grade level were also as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 41 publications
(96 reference statements)
2
69
0
1
Order By: Relevance
“…Given this evidence, one might conclude that there has been little return on investment for educational policy promoting testing and curriculum standardization in history education; however, previous research from Fitchett et al (2014aFitchett et al ( , 2014b has hinted otherwise. Analysis of elementary social studies indicated that testing was associated with increased time spent on the subject.…”
Section: School Policy Context and History Content Knowledgementioning
confidence: 81%
See 2 more Smart Citations
“…Given this evidence, one might conclude that there has been little return on investment for educational policy promoting testing and curriculum standardization in history education; however, previous research from Fitchett et al (2014aFitchett et al ( , 2014b has hinted otherwise. Analysis of elementary social studies indicated that testing was associated with increased time spent on the subject.…”
Section: School Policy Context and History Content Knowledgementioning
confidence: 81%
“…Descriptive statistics of the sample are included in Table 1. (Fitchett et al, 2014a(Fitchett et al, , 2014b. NAEP-USH provided quartile measures of school percentage free-reduced lunch and school percentage planning to attend a college/university.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A need exists to understand why some elementary teachers spend considerable time on social studies compared with their peers in the same state. Fitchett et al (2012) noted that "little research has analyzed the influence of teacher/school ecology factors and state policy on how much instructional time is allocated to social studies" (4). One such factor includes school culture, which Robbins and Alvy (1995) (Ackerman, Donaldson, and van der Bogert 1996;Deal andPeterson 1998, 1999).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Les représentations sociales des enseignants influencent les conceptions que ces derniers se font du savoir savant et des « bonnes » pratiques (Bouhon, 2007(Bouhon, , 2009Fitchett, Heafner et Lambert, 2014 (Bouhon, 2007 ;Demers, 2011 ;Moisan, 2010). L'importance des enjeux reliés à la certification donne un grand poids aux épreuves uniques ministérielles.…”
Section: Une éPreuve Qui Influence Les Pratiquesunclassified